Surgical Smile Makeover with an Unique Combination of the Lip Repositioning and Laser Depigmentation Techniques - Mathew, Sneha Mary (Journal of Orofacial Research, 2018)
An attractive smile is essential for a long-lasting impression. Excessive Gingival Display (EGD) during smiling and gingival pigmentation is a cause for concern to many individuals. Various treatment modalities are available to manage the